Potret Disabilitas dalam Novel Pasukan Matahari Karya Gol A Gong - Wiradi, Dedek; Hayati, Yenni (Universitas Negeri Padang, 2024)
Literary works are a reflection of the social reality that exists in the environment in which they are created. One of the problems of life that has received a lot of attention and has received various assessments from the community is the problem of disability. This research aims to describe: (1) the forms of disabilities borne by the characters in the novel Pasukan Matahari by Gol A Gong, (2) the causes of disabilities borne by the characters in the novel Pasukan Matahari by Gol A Gong, (3) the impact of disabilities borne by the characters in the novel by Gol A Gong. This research is a literary research using descriptive method. The data is in the form of words, phrases, clauses and sentences related to disability and in the form of narrator descriptions, character speech, character actions contained in the novel Pasukan Matahari by Gol A Gong. The results of this study are: (1) the form of disability carried by the characters in the novel Pasukan Matahari by Gol A Gong, consists of only one form of disability, namely physical disability (disability). (2) the cause of disability in the novel Pasukan Matahari by Gol A Gong only consists of one cause, namely an accident. (3) The impact of disability in the novel Pasukan Matahari by Gol A Gong consists of two impacts, namely: (a) social and emotional impacts, (b) physical and health impacts. The social-emotional impacts that occur to the characters are heartache, limited social activities, feeling a burden on others. While the physical and health impacts that occur to the character are physical differences with other people and must use assistive devices such as crutches.